Political Moral Decadence: An Islamic Legal Study on the Phenomenon of Transactional Politics in Indonesia - Pikahulan, Rustam; Abdul Hafid; Kurniati; Misbahuddin (Universitas Islam DDI AG.H. Abdurrahman Ambo Dalle, 2025)
This study examines the moral decline in Indonesian politics by focusing on transactional political practices that contradict Islamic law. Practices such as corruption and abuse of power have diminished political integrity and public trust. Using a normative legal approach, this research analyzes relevant regulations and Islamic legal principles of justice (‘adl) and trust (amanah). The findings reveal that transactional politics not only violate existing laws but also contradict the objectives of Islamic law (maqāṣid al-syarī‘ah), which emphasize justice, integrity, and social responsibility. From the perspective of Islamic law, political power is a trust that must be exercised for the welfare of the people, not for personal gain. Therefore, moral reform in politics should begin with Islamic ethical education, strengthened public accountability, and strict law enforcement to restore politics as a means of upholding justice and promoting social welfare.